PERBEDAAN HASIL BELAJAR AKUNTANSI KEUANGAN MENENGAH 1 ANTARA GAYA KOGNITIF âFIELD INDEPENDENT â DAN âFIELD DEPENDENT - Nunuk Suryanti (Universitas Negeri Malang, 2014)
This research purpose to examine whether there is difference of intermediate accountingÂ learning outcomes between âfield independentâ students and âfield dependentâ students . This study used survei approach. The population are from 288 accounting students with 167 samples. Instrument of studentâs cognitive style by GEFT. Studentâs academic achievement from accounting departmentâs data. The results showed that there is differences on the studentsâ intermediate accountingÂ learning outcomes between âfield independentâ students and âfield dependentâ students. Â